Process management in integrating and core areas of project management: case study in university professors. (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2019)
The university labor is based on three fundamental pillars: teaching, research and extension; these pillars are made up of routines activities, but also by projects carried out in order to achieve results with unique characteristics within limited timeframes and budgets, that is why these last require that the professors who perform them apply specific methodologies and tools, in addition to developing personal skills that allow obtaining the expected results. Within the proposed standards by the Project Management Institute are considered a group of processes and areas of knowledge that must be coordinated to manage a project, so this article, that is framed in a methodology of a descriptive type with a non-experimental design, has a main objective to diagnose, through a self-evaluation, the management carried out by the professors of the Services Technology Department of the Simon Bolivar University (USB) of the processes and areas of integrating and essentials (management of the scope, time, of cost and quality)of the projects that they develop in order to subsequently design a training plan in project management for university professors framed in their teaching development plan.
Keywords: processes management; knowledge areas; project management; university professors